Pengaruh Viral Marketing dan Neuromarketing terhadap Keputusan Pembelian Konsumen Fore Coffee - Khairunnisa, Dinda; Salqaura, Siti Alhamra; Lestari, Indawati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The purpose of this study was to determine: (1) the effect of Viral Marketing on purchasing decisions, (2) the effect of Neuromarketing on purchasing decisions, and (3) the simultaneous influence of Viral Marketing and Neuromarketing on purchasing decisions for Fore Coffee in Medan Polonia District. This research uses a quantitative approach with an associative research type. The data collection technique was carried out by distributing questionnaires to 100 respondents who had bought Fore Coffee. The data analysis technique uses multiple linear regression analysis. The results showed that: (1) Viral Marketing (X1) has a positive and significant effect on purchasing decisions (Y), indicated by the tcount> ttable value (5.622> 1.984) and a significance of 0.000 <0.05, (2) Neuromarketing (X2) also has a positive and significant effect with a tcount> ttable value (6. 147 > 1.984) and a significance of 0.000 <0.05, and (3) simultaneously, Viral Marketing and Neuromarketing have a positive and significant effect on Fore Coffee purchasing decisions, as evidenced by the Fcount value of 162.938> Ftable 3.09 and a significance of 0.000 <0.05.